The Responses of Lactobacillus reuteri LR1 or Antibiotic on Intestinal Barrier Function and Microbiota in the Cecum of Pigs - Yang, Bijing; Liu, Chunyan; Huang, Yanna; Wu, Qiwen; Xiong, Yunxia; Yang, Xuefen; Hu, Shenglan; Jiang, Zongyong; Wang, Li; Yi, Hongbo (Frontiers in Microbiology, 2022)
This study aimed to investigate responses of the Lactobacillus reuteri or antibiotic on the cecal microbiota and intestinal barrier function at different stages of pigs. A total of 144 weaned pigs (Duroc × Landrace × Yorkshire, 21 d of age) were randomly assigned to the control group (CON, fed a basal diet), the antibiotic group (AO, fed basal diet plus 100 mg/kg quinoline and 75 mg/kg aureomycin), and the L. reuteri group (LR, fed the basal diet +5×1010 CFU /kg L. reuteri LR1) throughout 164-d experiment. 45 cecal samples were collected for 16S rRNA gene amplicon. Results revealed that although LR and AO did not change the diversity of cecal microbiota in pigs, the abundance of some bacteria at the genus level were changed by age. The proportion of Lactobacillus were increased by LR in early life, whereas decreased by AO. The relative abundance of Ruminococcaceae and Lachnospiraceae were increased along with age. In addition, gas chromatography results demonstrated that ages, not AO or LR, has significant effects on the concentrations of SCFAs in the cecum of pigs (P<0.05). However, the mRNA expression of tight junction proteins zonula occluden-1 (ZO-1) and occludin were increased by AO in the cecum of pigs at 14 days, while LR increased the mRNA expression of intestinal barrier-related proteins ZO-1, occludin, mucin-1, mucin-2, PG1-5, and pBD2 in the cecum of pigs at 14 or 164 days (P<0.05). Moreover, intestinal community composition was significantly correlated with environmental factors such as ZO-1, occludin, mucin-2, and pBD2 in the cecum of pigs (P<0.001). In conclusion, LR and AO have different effects on the intestinal barrier function of the cecum, but have little effects on cecal microflora at different stages in pigs. The microflora and their metabolites SCFAs were significant changed along with age. These findings provide important information to understand the homeostasis of the cecum in pigs after antibiotic or probiotics treatment.